Pembuktian Kepemilikan Tanah Adat Minahasa Pasini Dalam Praktik Penyelesaian Sengketa Tanah Di Sulawesi Utara - Sondakh, Jemmy; Paransi, Eugenius; Ngantung, Cevonie Marietje (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The aim of the research is to find out the use of Pasini land by the Minahasa people. Pasini land ownership proof system in the settlement of land disputes in court at this time. By using normative legal research methods supported by empirical studies as legal facts about pasini soil, the following results are obtained. Pasini Land as a customary right still exists today. Pasini rights as original unwritten Indonesian law affect the use of limited pasini land which cannot be used as collateral for credit loans at the Bank. in proving ownership of pasini land is still very weak compared to land that has been certified as SHM because in principle customary law is an unwritten custom that does not yet have certainty law even though there has been an amendment to the 1945 Constitution Article 18 the position of customary rights Customary law is the same as the field of positive law that exists in this country. Conclusion The existence of pasini land as customary rights is still recognized especially with the amendment to Article 18 of the 1945 Constitution.